Menstrual Cycle in Women Who Co-use Marijuana and Tobacco. Issue 3 (May 2018) - Lammert, Sara; Harrison, Katherine; Tosun, Nicole; Allen, Sharon
Abstract : Objective: Marijuana is the most commonly used illicit drug in the United States and co-use with tobacco is increasing. Preliminary studies have indicated that marijuana may suppress luteinizing hormone (LH) or shorten the luteal phase. Although the literature is mixed, these sex hormones may play a role in smoking cessation outcomes. This secondary subgroup analysis aims to explore the menstrual cycle of females who co-use marijuana and tobacco compared with females who only use tobacco in a sample of tobacco treatment-seeking individuals. Methods: Female participants, aged 18 to 50 years, who self-reported regular menstrual cycles and co-use of marijuana and tobacco were matched 1:3 by age to participants who only use tobacco. Length of the follicular and luteal phases was determined using First Response Urine LH tests. Wilcoxon 2-sample t tests were used to determine differences in phase lengths between groups. Results: Thirteen women who co-use marijuana and tobacco, and 39 women who only use tobacco were included in this analysis. Overall, participants were 37.3 ± 8.0 (SD) years of age, mostly Caucasian (67%), and smoked 12.6 ± 5.2 (SD) cigarettes per day. The luteal phase length among participants who co-use marijuana and tobacco (11.4 days ± 2.2 [SD]) was significantly shorter than among participants who only use tobacco (16.8 days ± 11.3 [SD]; P  = 0.002). No differences were found in follicular phase length or menstrual cycle length. Conclusions: These data suggest that females who co-use marijuana and tobacco may have a shortened luteal phase in comparison with females who only use tobacco. Further studies are needed to better understand how marijuana use may impact the menstrual cycle and affect smoking outcomes.